1996
DOI: 10.1002/bjs.1800830606
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Should ice technique in inguinal hernia repair: A systematic review of controlled trials and a meta-analysis

Abstract: The Shouldice technique for inguinal hernia repair has been suggested by some authors as the best conventional method against which other methods using prostheses should be compared. The paper which follows is a systematic review involving a comprehensive search of the medical literature to identify all clinical trials (article or abstract) evaluating the Shouldice repair. After assessment of certain quality criteria, the best studies were pooled in a meta-analysis. Nine publications were found with 11 study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 11 publications
0
36
0
3
Order By: Relevance
“…In 1994, in a randomized controlled trial (RCT) comparing modified Bassini versus Shouldice inguinal hernia repair, the recurrence rates after 3.3 years were 9.6% for the Bassini technique and only 1.7% for a Shouldice operation [3]. In 1996, in a systematic review of controlled trials and a meta-analysis, Simons et al [4] found that the relative risk ratio (risk of developing a recurrence) for pooled studies (n=2,500) was 0.62 (95% confidence interval, 0.44-0.87) in favor of the Shouldice technique. Thus, the Shouldice technique should be used when a non-mesh repair is considered (grade A).…”
Section: Grades Of Recommendationmentioning
confidence: 96%
“…In 1994, in a randomized controlled trial (RCT) comparing modified Bassini versus Shouldice inguinal hernia repair, the recurrence rates after 3.3 years were 9.6% for the Bassini technique and only 1.7% for a Shouldice operation [3]. In 1996, in a systematic review of controlled trials and a meta-analysis, Simons et al [4] found that the relative risk ratio (risk of developing a recurrence) for pooled studies (n=2,500) was 0.62 (95% confidence interval, 0.44-0.87) in favor of the Shouldice technique. Thus, the Shouldice technique should be used when a non-mesh repair is considered (grade A).…”
Section: Grades Of Recommendationmentioning
confidence: 96%
“…At specialized centres like the Shouldice Hospital, reported recurrence rates are fewer than 1% [5,6]. Those excellent results hardly reflect the reality of general health care [7,8] but underline surgical expertise as an important risk factor.…”
Section: Introductionmentioning
confidence: 93%
“…Under trial circumstances, the traditional open repairs (Bassini, McVay, Shouldice) have recurrence rates of 0-11% [15]. The time for return to work after these operations tends to be as long as 4-9 weeks after surgery [12,17].…”
Section: Abstract: Inguinal Hernia -Cost Analysis -Laparoscopic Hernmentioning
confidence: 99%